Rectal prolapse and urinary retention: A case report of an "anal cystocele" - Maria E. Florian-Rodriguez; Kinjal Mehta; Gaurav Khatri; Joseph I. Schaffer (Elsevier, 2019)
Background: Concomitant rectal and vaginal prolapse is diagnosed in 14-55% of patients who present for pelvic floor evaluation.Case: A patient was referred for pelvic floor evaluation in the setting of rectal prolapse and urinary retention. Preoperative magnetic resonance (MR) imaging revealed the presence of a posterior cystocele prolapsing through the full-thickness rectal prolapse. Conclusion: Rectal prolapse with concomitant urinary retention should raise suspicion for posterior bladder prolapse. Here we propose the new term "anal cystocele". MR imaging aids in the diagnosis and treatment planning for this condition. Keywords: Rectal prolapse, Urinary retention, Cystocele